Perancangan Aplikasi Point Of Sales (POS) Pada Apotek Mitra Sejahtera Berbasis Web - Nugraha, Adhy (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
Advances in computer technology can be utilized in various fields, one of which is the Point Of Sales (POS) software technology. Point Of Sales (POS) software is widely used in sales, where sales are an important form of service, including at pharmacies. Pharmacy is one of the trading businesses in the health sector that also requires a data processing system to simplify and expedite its performance. One of the pharmacies that use conventional methods is Apotek Mitra Sejahtera having its address at Jl. Kesehatan No. 40 Majalengka. The sale and purchase process is conventionally considered to slow down the performance of pharmacy services, so the Point Of Sales (POS) application is implemented which can help and facilitate the transaction process for buying and selling drugs. The programming used for making this application is PHP using the Laravel framework and MySQL as the database. The purpose of this study is to determine whether the design of the Point Of Sales (POS) application at Mitra Sejahtera Pharmacy can function properly and help the transaction process. The development method used is the RUP (Rational Unified Process). The results of implementing the Point Of Sales (POS) application at Apotek Mitra Sejahtera can improve the performance and service of the Pharmacy to be more effective and efficient.